INCREASING THE Z GENERATION’S REVENUE THROUGH CREATIVE WASTE RECYCLING AND SUSTAINABILITY AWARENESS PAINTING KIT BUSINESS - Memarista, Gesti; Isabella, Madeline; Kurniawan, Hans Michael; Sisworo, Michael Verdian Tanto (FEB Universitas Sam Ratulangi Manado, 2024)
High business innovation and the increasing creativity of Generation Z have allowed students to own businesses. In the Student Creativity Program (PKM), generation Z can increase their income by creating innovative products from recycled waste. The Faculty of Business, Widya Mandala Catholic University, Surabaya students have the opportunity to obtain a PKM grant by making a Painting Kit. This product has a unique canvas innovation. The development of this product involves making canvas from paper pulp. The purpose of this innovation is to reduce organic waste. The subjects on the canvas in the form of motifs printed on the canvas are cute pictures such as animals, flowers, and scenery so that they can attract consumers, especially children. With this innovation, paper waste which is an environmental problem will be processed into aesthetic works of art and has added value. The products of this student's creativity are patterned canvases, easels, and painting equipment form. Students will get increased income from this business idea. In addition, the Painting Kit is also useful for mental health by buying a Painting Kit, namely filling free time with painting and practically there are equipment available and coloring according to the numbers on the canvas and paint.